Lecturers’ Motivational Strategy in ESP Classroom - Afif Ikhwanul Muslimin (EDULANGUE, 2018)
Abstract: This study is aimed to investigate how teachers’ motivational strategies use in ESP classrooms in the success of language teaching. Hence, the present study is trying to examineteachers’ motivationalstrategies and their reasons in ESP classrooms in teaching EnglishatFDIK UIN Mataram from their point of views. This research employed descriptive qualitative design on lecturers’ motivational strategies in ESP classrooms. The subjects of this study are four lecturers of ESP classes representing each departmentsat faculty of dakwah and communication science (FDIK) ofUIN Mataram. Management dakwahdepartment, Islamic community development department, Islamic counseling guidance department, and Islamic communication and broadcasting department. Then, it was found that ESP teachers in FDIK UIN Mataram generally employ all Ten Commandments for motivating language learner as proposed by Chengand Dornyei(2007). Further, researcher found additional motivational strategy appeared in lecturer no 3that interview strategy is not belong to the ten commandment but also stated in Chengand Dörnyei (2007)as main instrument, it is promoting self-motivating learner strategy. Finally, the reasons why the teachers consider to use those motivational strategies are: (1) bringing teaching practicality and interaction to be easier, more comfortable, and being more fun, (2) creating students’ awareness on the future success, (3) showing their care on students’ learning improvement and interest, and (4) being fair and wise in assessment. Keywords: Lecturers’ motivational strategy, and ESP Classroom